Study on Car Parking Issue of Egyptian Cities - Amer, Abdelwahab Mohamed; Elalfy, Ayman; Farrag, Nermin Mokhtar (Research Aspects in Arts and Social Studies Vol. 9, 2023)
Car parking is now a major issue in both developed and developing countries' metropolitan areas. Many cities are currently suffering from a lack of parking spaces, which is being caused by an increase in car ownership. The root cause of urban car parking issues is an imbalance between parking availability and demand. Part of the reason for this mismatch is due to insufficient land use future planning and an underestimation of future car parking needs. The current study focuses on the city's parking problem, particularly in Egyptian cities. In this respect, the study begins by listing some present major car parking problems in Cairo as an instance of Egyptian cities, demonstrating their different causes and current tried-and-true – but ineffective – solutions. The study focuses on some methods for resolving car parking issues in Egyptian cities along three major axes: planning, management, and new car parking technologies. Parking solutions in cities varies depending on the nature of each of its districts and its facilities. The study concluded with some recommendations to help ease Egyptian cities' car parking problems, based on a study of some current planning and management trends and innovative technical solutions. Suggests a method for achieving larger community goals like enhancing urban mobility and trying to make cities more livable and efficient.